JIU-JITSU AND MUAY THAI: BUILDING IDENTITIES (Fiep Bulletin - online, 2015)
We have tried, in this project, to identify through semi-structured interviews the reasons that took men already over thirty years of age to start practising jiu-jitsu and muay thai . This survey is justified by assumptions on the study of masculinity defended by (MOSSE, 1996; BOURDIER, 2002; MONTESINOS, 2002). These studies affirm there is relation between the need of complying with social demands as to posture and masculine image: strong and manly. We apprehend from the speech of three men who practise jiu-jitsu and three who practise muay thai that family influence was vital for them, while in their childhood, to be inserted into a recognised masculine culture: the practice of physical activities such as fighting and sport. However, in adult life other interests arose  mutually justified associated interests. To keep a youthful appearance and posture seems to justify the premiss that youth is one of the foundations of masculinity. Visible youth associates with other virtues appreciated in our society  talent, health and youthfulness. We consider these motivations in favour of the practice of martial arts as vital since they attempt to demystify the violence that surrounds martial arts. Our interviewed cases' subliminal message is that by practising martial arts they recovered their essential balance to deal with everyday life and they mingle with other groups while they preserve their self-esteem.
Keywords: masculinity; jiu-jitsu; muay thai.